2′-Deoxy-5-(hydroxymethyl)cytidine: estimation in human cancer cells with a simple chemosensor. Issue 70 (29th November 2018) - Sarkar, Himadri Sekhar; Kundu, Shampa; Das, Sujoy; Maiti, Pulak Kumar; Mandal, Sukhendu; Sahoo, Prithidipa
Abstract : A new chemosensor, CS-1, has been developed and characterized for the selective detection and quantification of 2′-deoxy-5-(hydroxymethyl)cytidine (5hmC) in human cancer cells. Abstract : A pyrrole-based rhodamine conjugate (CS-1 ) has been developed and characterized for the selective detection and quantification of 2′-deoxy-5-(hydroxymethyl)cytidine (5hmC) in human cancer cells with a simple chemosensing method.